Shear-induced chemical segregation in a Fe-based bulk metallic glass at room temperature - D. V. Louzguine-Luzgin (Nature Portfolio, 2021)
Abstract Shear-induced segregation, by particle size, is known in the flow of colloids and granular media, but is unexpected at the atomic level in the deformation of solid materials, especially at room temperature. In nanoscale wear tests of an Fe-based bulk metallic glass at room temperature, without significant surface heating, we find that intense shear localization under a scanned indenter tip can induce strong segregation of a dilute large-atom solute (Y) to planar regions that then crystallize as a Y-rich solid solution. There is stiffening of the material, and the underlying chemical and structural effects are characterized by transmission electron microscopy. The key influence of the soft Fe–Y interatomic interaction is investigated by ab-initio calculation. The driving force for the induced segregation, and its mechanisms, are considered by comparison with effects in other sheared media.